Kidney machine perfusion is associated with improved long-term graft survival mediated by reduced delayed graft function: a mate-kidney analysis - Cojuc-Konigsberg, Gabriel; Chopra, Bhavna (Artificial organs, 2025)
Background Kidney machine perfusion (MP) prevents delayed graft function (DGF). Whether this benefit translates into improved long-term graft survival (LGS) remains uncertain. We evaluated the association between MP and LGS and its potential mediation by DGF. Methods UNOS analysis of adult deceased donor kidney transplant recipients (KTRs) from January 2010 to June 2019. We selected KTRs with cold ischemia time (CIT) > 12 h and on tacrolimus maintenance. We included KTRs from dual-kidney donors and compared outcomes where one mate kidney received MP and the other did not. The primary endpoint was all-cause graft failure (GF) analyzed using a stratified multivariable Cox proportional hazards model. We assessed the association of MP and DGF with conditional logistic regression. We evaluated the mediation effect of DGF by combining the predictor and outcome models and bootstrapping with 1000 iterations to calculate 95% confidence intervals (CI). Results We included 2355 mate-kidney pairs with 5.8 years (IQR 4-8) median follow-up. MP was associated with lower GF risk (aHR 0.86, 95% CI 0.75-0.98) and DGF odds (aOR 0.41, 95% CI 0.34-0.51) than no MP. DGF fully mediated the association between MP and GF, as the effect was no longer statistically significant after adjusting for DGF (aHR 0.89, 95% CI 0.78-1.03). DGF explained 76.8% of the association between MP and GF. Conclusions In mate-kidney pairs with discordant MP use and CIT > 12 h, MP was associated with decreased GF risk, mediated by decreased DGF likelihood. MP both mate kidneys with CIT > 12 h should be considered to potentially improve LGS.
Gesehen am 11.02.2026